ASPECTS OF HISTORICAL ROMANIAN DRAMATURGY DURING THE COMMUNIST TOTALITARIAN REGIME (Analele Universității din București - Istorie, 2024)
An insight that can greatly help us in our understanding of Romanian history during the era of the Communist totalitarian regime, is without a doubt provided by the historical dramaturgy of the period. During those years, a large number of historical plays were written and directed. It is for this very reason that historical theatre cannot be ignored by any historian interested in how the social representation of the past was constructed in the context of the four decades in which Romania was held in the grip of Communist ideology.There is an obvious parallel between the evolution of Romanian literature during the period in question (including dramaturgy) and Romanian historiography. In the latter field, changes that occurred during the 1960s and 1970s have been highlighted over the last two decades by Lucian Boia1. An analysis of literary criticism and writings revealssimilar characteristics and developments in that field. Moreover, the literary genre of historical theatre can be closely linked to the rise of nationalism within the political discourse of the Communist regime, so it should not come as any surprise that the number of historical themes had been growing steadily since the mid-1960s. In a manner similarto other cultural policies of the time, the ideological twists and turns of Romanian Communism can be found in the evolution of historical theatre. Indeed, the closest comparison that can be made is with the historical cinematography of the time, which was better known and more popular than the dramaturgy of the era, through its themes, subjects and artistic approaches.However, while the historical movies of the era are still available today and indeed are frequently broadcast on Romanian TV, the historical plays of the time are available to the modern researcher only in specialized books in which they had been collected before 1989, in the volumes of literary criticism from the Communist period, or in the collectivememory of witnesses.Nevertheless, a study of the impact of theatre under the conditions of communist totalitarianism is essential in order to be able to properly understand the effects of the regime’s propaganda, its evolution in terms of ideological orientation, and how it contributed to the crystallization of social representations of the past. This research study is merely a first step. The themes of the historical plays written and produced during the Communist regime are closely correlated with its historiographical writings. Ideas such as the antiquity of the Romanian nation, its persistency, the permanent nature of the defence of its statehood, and the aspiration toward unity are all now emerging. One theme highlighted during the 1970s is that of ‘heroism’, also present in the propaganda of the time. This theme channels us towards a better understanding of the role and attributes of the leader, thus becoming one of the main themes of Romanian historical dramaturgy within a very short time. While a long line of voivodes and heroes appeared on the stage, and via this medium through history, they became in fact the moving parts of a bigger mechanism that would ultimately become the personality cult of Nicolae Ceaușescu.
Keywords: representation of the past; historiography; history of Romanian literature; theatre in the communist era; heroism in Communist Art; communist propaganda; The attributes of the leader